Avaiação da Dor e da Postura em Pacientes com Lombalgia Submetidos a Dois Protocolos de Fortalecimento Abdominal - Camargo, Gabriela Machado [UNESP]; Marques, Ana Elisa Zuliani Stroppa [UNESP]; Pedroni, Cristiane Rodrigues [UNESP] (My University, 2012)
Introduction: the lumbar spine is the main part of the body responsible for the support of the loads, where approximately half of body weight is in stable balance. This support relates to the action of abdominal muscles, of great importance in the balance of that region. The existence of abdominal muscle weakness, such won’t perform its function, may induce pathological postural attitude, that predispose the pain. Objective: to compare the effects of two abdominal strengthening protocols on pain and postural alignment in individuals with low back pain. Method: participated of the study 21 individuals of both genders, with ages between 19 and 25 years old (average 21,8±1,5) and average Body Mass Index (BMI) 21,9 (±2,48), divided randomly in isometric abdominal stimulation group (n=8), abdominal strengthening group (n=7) and control group (n=6). They realized eight sessions of strengthening, when responded Visual Analogue Scale (VAS) before and after each intervention. The control group (n=6) had no intervention. The postural data had been analyzed by photogrammetry. Results: Pain and posture data were analyzed using paired t test, with signifi cance index of 5%. Postural angles had no signifi cant differences (p>0,05) from all angles analyzed after the intervention to none of the groups. For pain values, a signifi cant decrease (p<0,05) was observed since the fi fth session in patients who were treated by the abdominal exercises protocol, and the fi rst session in patients who were treated by the isometric abdominal stimulation protocol. However, this decrease in pain was immediate, not lasting along the treatment sessions, in both protocols. Conclusion: the proposed protocols did not interfere in postural alignment. They were effective to decrease pain in a same session, once the isometric was the most effective, but they weren’t effective in preserving the improves over time.

Introdução: A coluna lombar é a principal região do corpo responsável pela sustentação das cargas, onde, aproximadamente, metade do peso corporal se encontra em equilíbrio estável. Esse suporte se relaciona com a ação dos músculos abdominais, de grande importância no equilíbrio dessa região. Na existência de fraqueza abdominal, tal musculatura não desempenhará seu papel, que pode induzir atitude postural patológica, e predispõe a dor. Objetivo: comparar os efeitos de dois protocolos de fortalecimento abdominal sobre a dor e o alinhamento postural em indivíduos com lombalgia. Método: Participaram do estudo 21 indivíduos de ambos os gêneros, com idades entre 19 e 25 anos (média de 21,8±1,5) e Índice de Massa Corporal (IMC) médio de 21,9 (±2,48), divididos aleatoriamente em grupo de estimulação abdominal isomé- trica (n=8), grupo de fortalecimento abdominal (n=7) e grupo controle (n=6). Realizaram oito sessões de fortalecimento, respondendo Escala Visual Analógica (EVA) antes e após cada intervenção. O grupo controle não teve intervenção. Os dados posturais foram analisados por fotogrametria. Resultados: Os dados de dor e postura foram analisados por meio de teste t pareado, considerando índice de signifi cância de 5%. Nos ângulos posturais, não houve diferenças signifi cativas (p>0,05) em todos os ângulos analisados após a intervenção para nenhum dos grupos. Para os valores de dor, uma diminuição signifi cativa (p<0,05) foi observada a partir da quinta sessão nos pacientes que realizaram o tratamento com o protocolo de exercícios abdominais, e a partir da primeira sessão nos pacientes que executaram a estimulação abdominal isométrica. No entanto, essa diminuição da dor foi apenas imediata, não permanecendo nos valores reduzidos ao longo das sessões de tratamento, nos dois protocolos. Conclusão: os protocolos propostos não interferiram no alinhamento postural. Foram efi cazes para diminuir a dor em uma mesma sessão, sendo o isométrico mais efi caz, mas não foram na manutenção dessa melhora ao longo do tempo.
Evaluation of pain and posture in low back pain patients treated by two protocols of abdominal strengthening
Keywords: lombalgia; postura; músculos abdominais